Lithium oxide-containing positive electrode material precursor, lithium oxide-containing positive electrode material, preparation method thereof and use thereof, positive electrode sheet and use thereof

By preparing high-pressure strength lithium-oxygen positive electrode material precursor and using specific microstructure control and adding regulators, the problem of fragility of the positive electrode material during the manufacturing and charging and discharge process is solved, and higher cycle stability and safety performance are achieved.

JP2025511658AActive Publication Date: 2025-04-16BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024558144
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-09-23
Publication Date
2025-04-16
Estimated Expiration
2042-09-23

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials are fragile during the manufacturing process, resulting in a degradation of battery performance. Especially during the charging and discharging cycle, the material structure is unstable, which increases lateral reactions and reduces cycling and safety performance.

Method used

By preparing lithium oxygen positive electrode material precursor with high pressure strength, using specific microstructure control and adding appropriate regulators, the crushing index and stability of the positive electrode material are improved, thereby reducing material damage during the manufacturing process and maintaining structural stability during the charge and discharge process.

Benefits of technology

It improves the crushing index and cycle stability of lithium oxygen cathode materials, extends the cycle life of the battery, and improves the safety performance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511658000001_ABST
    Figure 2025511658000001_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion batteries, and discloses a lithium oxide-containing positive electrode material precursor, a lithium oxide-containing positive electrode material and its preparation method and use, and a positive electrode sheet and its use. 100 ) is Δλ(P 100 )≧60%+(y / x)×5%, where y / x is the molar ratio of Mn / Ni in the positive electrode material. The lithium oxide-containing positive electrode material has high crushing strength and stability, and can withstand high pressure during the preparation of the electrode sheet with only slight fracture, and can continue the lithium ion release / absorption reaction without serious rupture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of lithium ion battery technology, in particular to lithium oxide-containing positive electrode material precursor, lithium oxide-containing positive electrode material and its preparation method and use, positive electrode sheet and its use. [Background technology]

[0002] In recent years, new energy vehicles, as a national strategic emerging industry to cope with environmental pollution and the energy crisis, have shown favorable conditions for vigorous development. As a new energy carrier with excellent comprehensive performance, lithium-ion batteries have been widely applied in markets such as electric vehicles, energy storage power stations, communications and digital electronic products.

[0003] In lithium-ion batteries, the positive electrode is the core material of the lithium-ion battery, and it directly determines the technical performance level of the battery. Among the common lithium-ion battery positive electrode materials, LiNi 1-x-y Co x Mn y O2(NCM) and LiNi 1-x-y Co x Al y O2 (NCA) and lithium-rich manganese-based materials (LMR) have attracted attention and are being researched due to their high specific capacity and energy density. However, in order to obtain a higher volumetric energy density and integrated electrochemical performance, the positive electrode material needs to be roll-pressed with high strength during the battery electrode sheet fabrication process to obtain a high electrode density. Positive electrode materials with low strength are easily crushed or crushed during this process, which increases the contact area with the electrolyte and side reactions, deteriorating cycle performance and rate characteristics. In addition, during battery use, Li + Repeated desorption of the electrolyte causes the volume expansion and contraction of the layered structure, which causes the low-strength cathode material to be powdered, resulting in insufficient contact between the particles and the continuous formation of new electrolyte layers, which leads to increased side reactions and the deterioration and failure of the battery performance.

[0004] Therefore, developing new preparation methods, adjusting the microstructure of the layered positive electrode material, and increasing the crushing strength or particle strength of the positive electrode material are of great significance in achieving long cycle life, high specific capacity, high rate capability, etc. of the battery. Summary of the Invention [Problem to be solved by the invention]

[0005] The object of the present invention is to provide a lithium oxide-containing positive electrode material precursor, a lithium oxide-containing positive electrode material, a preparation method and use thereof, and a positive electrode sheet and use thereof, in order to overcome the defects existing in the conventional technology, that is, the lithium-containing metal oxide material is broken during the preparation of the electrode sheet, or the secondary particles are broken during the charge and discharge cycle, resulting in poor rate characteristics, deteriorated cycle performance, and reduced safety performance. The lithium oxide-containing positive electrode material has high crushing strength and stability, and while withstanding high pressure during the preparation of the electrode sheet, only slight fracture occurs, and the lithium ion release / absorption reaction can continue without serious rupture. [Means for solving the problem]

[0006] In order to achieve the above object, a first aspect of the present invention provides a lithium oxide-containing positive electrode material, the crushing exponent Δλ(P 100 ) is Δλ(P 100 ) ≧ 60% + (y / x) × 5% is satisfied, Here, y / x is the molar ratio of Mn / Ni in the positive electrode material.

[0007] A second aspect of the present invention provides a lithium oxide-containing positive electrode material precursor, wherein the precursor has a crushing exponent Δλ′(P 50 ) is Δλ´(P 50 ) ≧ 35% + (v / u) × 8%, where v / u is the molar ratio of Mn / Ni in the precursor.

[0008] The third aspect of the present invention provides a method for preparing a lithium oxide-containing positive electrode material, where the preparation method includes: uniformly mixing a precursor having a chemical formula represented by formula (1), a lithium source, and an optional element M2-containing additive, and performing primary sintering in an atmosphere furnace to obtain a primary sintered material having a chemical formula represented by formula (2) in S1; uniformly mixing the primary sintered material and an element M'-containing additive, and performing secondary sintering on the mixed material in an atmosphere furnace to obtain a lithium-containing metal oxide having a chemical formula represented by formula (3) in S2, Ni u Mn v M 1γ (OH)2, formula (1) where u + v + γ = 1, 0.2 < u < 1, 0 < v ≤ 0.75, 0 ≤ γ ≤ 0.35, M1 is at least one element selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, Na, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B, Li[Li a Ni x Mn y M j O2, formula (2) Li[Li a Ni x Mn y M j O2@M′, formula (3) where in formula (2) and formula (3), a + x + y + j = 1, 0 ≤ a ≤ 0.3, 0.2 < x < 1, 0 < y ≤ 0.75, 0 < j ≤ 0.35, M includes the M1 element in the precursor and the M2 element introduced during the primary sintering process, M1 and M2 may be the same or different, and each is at least one element selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B, in formula (3), M' is an oxide, phosphide, sulfide, fluoride or chloride containing at least one element selected from the group consisting of Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta and B, and the molar content of cations in M' is w, 0 <w / (a+x+y+j)≦0.1である。

[0009] A fourth aspect of the present invention provides a lithium oxide-containing positive electrode material prepared by the above-mentioned method for preparing a lithium oxide-containing positive electrode material.

[0010] A fifth aspect of the present invention provides a cathode sheet comprising at least 90 wt % of a lithium oxide-containing cathode material, based on the total weight of the cathode sheet; Here, the lithium oxide-containing positive electrode material is the lithium oxide-containing positive electrode material described above.

[0011] A sixth aspect of the present invention provides the use of the lithium oxide-containing positive electrode material as described above, the lithium oxide-containing positive electrode material precursor as described above, or the positive electrode sheet as described above in a lithium ion battery.

[0012] Through the above technical solutions, the present invention has the following advantages: (1) The lithium oxide-containing positive electrode material and precursor of the present invention realize high crystallinity and densification of the precursor by controlling a specific microstructure, thereby improving the crushing index of the positive electrode material; (2) The present invention improves the crush index, cycle life and safety performance of the material through suitable modifiers and doping elements; (3) The sintering precision in the preparation process of the lithium-containing metal oxide of the present invention affects the crushing index of the material, so when selecting the sintering precision, it is necessary to balance the cost, the material crushing index, the material physical index and the electrochemical performance. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic diagram for comparing charge / discharge curves in Example 5 and Comparative Example 1. [Diagram 2]FIG. 11 is a schematic diagram for comparing the cycle performance of Example 5 and Comparative Example 1. [Diagram 3] FIG. 11 is a schematic diagram for comparing charge / discharge curves in Example 5 and Comparative Example 2. [Figure 4] FIG. 11 is a schematic diagram for comparing the cycle performance of Example 5 and Comparative Example 2. [Diagram 5] FIG. 11 is a schematic diagram for comparing charge / discharge curves in Example 5 and Comparative Example 3. [Figure 6] FIG. 11 is a schematic diagram for comparing the cycle performance of Example 5 and Comparative Example 3. [Figure 7] FIG. 11 is a schematic diagram for comparing charge / discharge curves in Example 5 and Comparative Example 4. [Figure 8] FIG. 11 is a schematic diagram for comparing the cycle performance of Example 5 and Comparative Example 4. [Figure 9] FIG. 13 is a schematic diagram for comparing charge / discharge curves in Example 9 and Comparative Example 5. [Figure 10] FIG. 13 is a schematic diagram for comparing the cycle performance of Example 9 and Comparative Example 5. [Figure 11] FIG. 13 is a schematic diagram comparing charge / discharge curves in Example 9 and Comparative Example 6. [Figure 12] FIG. 13 is a schematic diagram for comparing the cycle performance of Example 9 and Comparative Example 6. [Figure 13] FIG. 13 is a schematic diagram comparing charge / discharge curves of Example 9 and Comparative Example 7. [Figure 14] FIG. 13 is a schematic diagram for comparing the cycle performance of Example 9 and Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The endpoints of the ranges and any values ​​disclosed herein should be understood not to be limited to such exact ranges or values, but to include values ​​close to these ranges or values. In the case of ranges of numerical values, the endpoints of each range, and the endpoints of each range and any single point value, and the single point values ​​may be combined with each other to obtain one or more new numerical ranges, and these numerical ranges are deemed to be specifically disclosed in the specification.

[0015] Conventional lithium-containing metal oxide materials for lithium-ion batteries need to be subjected to high pressure during the preparation of electrode sheets. In addition, during continuous charge-discharge cycles, the materials lack crush strength or have unstable structures, leading to bursting and increased side reactions with the electrolyte, accelerating the consumption of the electrolyte and the dissolution of transition metal cations in the positive electrode material, resulting in reduced cycle performance, safety performance and capacity, and ultimately battery failure.

[0016] As described above, a first aspect of the present invention provides a lithium oxide-containing cathode material, wherein the crush exponent Δλ (P 100 ) is Δλ(P 100 ) ≧ 60% + (y / x) × 5% is satisfied, Here, y / x is the molar ratio of Mn / Ni in the positive electrode material.

[0017] JPEG2025511658000002.jpg53170

[0018] JPEG2025511658000003.jpg20170

[0019] According to the present invention, preferably, the crushing exponent Δλ(P 200 ) is Δλ(P 200 ) ≧ 45% + (y / x) × 5%.

[0020] According to the present invention, more preferably, the crushing exponent Δλ(P 300 ) is Δλ(P 300 ) ≥ 35% + (y / x) × 5%.

[0021] According to the present invention, it is still possible to determine whether Δλ(P 100 ) indicates the crushing index of the material when the material has a compressive strength P = 100Mpa, and Δλ(P 200 ) indicates the crushing index of a material when the material has a compressive strength P = 200 MPa, and is inferred from this.

[0022] The positive electrode material according to the present invention has excellent crushing strength, is difficult to rupture, has a stable structure, few side reactions, and excellent safety performance and capacity retention rate during the process of being used as a positive electrode.

[0023] According to the present invention, the lithium oxide-containing positive electrode material has a chemical formula represented by formula (3), Li[Li a Ni x Mn y M j O2@M′, formula (3) Here, a + x + y + j = 1, 0 ≦ a ≦ 0.3, 0.2 < x < 1, 0 < y ≦ 0.75, 0 < j ≦ 0.35, M is at least one selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta and B, M′ is an oxide, phosphide, sulfide, fluoride or chloride containing at least one element of Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta and B, the molar content of the cation in M′ is w, and 0 < w / (a + x + y + j) ≦ 0.1.

[0024] According to the present invention, preferably, 0.02 ≦ a ≦ 0.3, 0.3 < x < 0.9, 0.05 < y ≦ 0.68, 0 < j ≦ 0.3, 0.001 < w / (a + x + y + j) ≦ 0.02.

[0025] According to the present invention, M is at least one selected from Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Ta and B, and M′ is an oxide, phosphide, sulfide or fluoride containing at least one element of Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Ta and B.

[0026] In the present invention, the inventor of the present invention has discovered that by adopting an appropriate modifier, the crushing strength and stability of the material particles can be enhanced, the DC internal resistance value and the gas generation amount of the material during the cycle process can be reduced, and the cycle life of the material can be improved.

[0027] By doping with elements such as Ti, Sc, Zr, W, Mg, Y, Co, Cr, Ta, the crystal structure of the material can be stabilized, the microzone structure of the material can be improved, and the crushing index, cycle life and safety performance of the material can be improved. By doping with elements such as Ti, Zr, Nb, La, W, Co, B, the surface of the material particles or the interface between the particles can be formed with lithium-containing compounds (e.g. LiNbO3 or Li2ZrO3 or Li4Ti5O 12 or Li3BO3 or LaNiO3, etc., to stabilize the surface structure of the material particles, the interfacial strength between the particles, or the grain boundary structure between the primary crystal grains, thereby improving the crushing index and cycle life of the material, and accelerating the transport of lithium ions between the particles and between the interfaces, thereby improving the rate characteristics of the material.

[0028] According to the present invention, the tap density of the positive electrode material is ≧1.7 g / cm 3 and preferably ≧2 g / cm 3 and more preferably ≧2.4 g / cm 3 It is.

[0029] According to the present invention, the compaction density of the positive electrode material is ≧2.8 g / cm 3 and preferably ≧3 g / cm 3 and more preferably ≧3.2 g / cm 3 It is.

[0030] According to the present invention, the content of the surface soluble alkali of the positive electrode material is: Li2CO3≦1wt%, LiOH≦0.5wt%, Preferably, Li2CO3≦0.5wt%, LiOH≦0.4wt%, More preferably, Li2CO3≦0.3wt%, LiOH≦0.3wt%, Even more preferably, Li2CO3≦0.2wt% and LiOH≦0.2wt% are satisfied.

[0031] According to the present invention, the positive electrode material has a half-width FWHM of the (003) crystal plane obtained by XRD.(003) and FWHM of (104) crystal plane (104) teeth, 0.10≦FWHM (003) ≦0.25, preferably 0.13≦FWHM (003) ≦0.22, 0.20≦FWHM (104) ≦0.50, preferably 0.22≦FWHM (104) ≦0.42.

[0032] According to the present invention, the positive electrode material has a peak area S of the (003) crystal plane obtained by XRD. (003) and the peak area S of the (104) crystal plane (104) teeth, 1.1≦S (003) / S (104) ≦1.8, preferably 1.2≦S (003) / S (104) ≦1.6.

[0033] In the present invention, in addition to using appropriate additives, the precursor morphology and microstructure are controlled to achieve high crystallinity and densification of the precursor, thereby improving the crushing index of the positive electrode material.

[0034] A second aspect of the present invention provides a lithium oxide-containing cathode material precursor, wherein the crush exponent Δλ′(P 50 ) is Δλ´(P 50 ) ≧ 35% + (v / u) × 8%, where v / u is the molar ratio of Mn / Ni in the precursor.

[0035] According to the invention, it is preferred that the crushing index Δλ′(P 100 ) is Δλ´(P 100 )≧25%+(v / u)×8%.

[0036] According to the present invention, Δλ′(P 50 ) indicates the crushing index of the precursor material when the precursor material has a pressure strength P = 50 MPa, and Δλ'(P 100) shows the crushing index of the precursor material when the precursor material has a pressure strength P = 100 MPa, and the following can be inferred from this.

[0037] JPEG2025511658000004.jpg58170

[0038] JPEG2025511658000005.jpg24170

[0039] According to the present invention, the precursor has a chemical formula represented by formula (1), Ni u Mn v M γ (OH)2, formula (1), where u + v + γ = 1, 0.2 < u < 1, 0 < v ≤ 0.75, 0 ≤ γ ≤ 0.35, and M is at least one selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, Na, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B, Preferably, 0.3 ≤ u ≤ 0.9, 0.05 ≤ v ≤ 0.68, 0 ≤ γ ≤ 0.3, and M is at least one selected from Ti, Al, Zr, W, Co, Nb, La, Na, and Mg. In the present invention, by doping elements such as Ti, Al, Zr, W, Co, Nb, La, Na, and Mg, the internal or surface structure of the microzone of the precursor can be stabilized.

[0040] The characteristics of the precursor material according to the present invention are further as follows.

[0041] According to the present invention, more preferably, the tap density of the precursor ≥ 1.2 g / cm 3 , preferably ≥ 1.6 g / cm 3 , still more preferably ≥ 2 g / cm 3 .

[0042] According to the present invention, the BET value of the specific surface area of the precursor satisfies BET ≤ 30 m 2 / g, preferably, BET ≤ 25 m 2 / g.

[0043] According to the invention, the particle size distribution coefficient K 90 0.5≦K 90 ≦1.6, where K 90 =(D 90 -D 10 ) / D 50 And D 10 , D 50 and D. 90 indicate the particle size values ​​when the particle cumulative volume distribution is 10%, 50%, and 90%, respectively.

[0044] According to the invention, the precursor has a half-width FWHM of the (001) crystal plane obtained by XRD. (001) , FWHM of (100) crystal plane (100) and FWHM of (101) crystal plane (101) teeth, 0.3≦FWHM (001) ≦1, preferably 0.5≦FWHM (001) ≦0.8, that is, the precursor material according to the present invention satisfies FWHM measured by an X-ray diffraction device. (001) 2θ is 0.3 or more and 1 or less, preferably 0.5 or more and 0.8 or less, 0.10≦FWHM (100) ≦0.5, preferably 0.25≦FWHM (100) ≦0.35, 0.30≦FWHM (101) ≦1.0, preferably 0.4≦FWHM (101) ≦0.8.

[0045] According to the present invention, the precursor has a peak area S of the (001) crystal plane obtained by XRD. (101) and the peak area S of the (101) crystal plane (104) is S (001) / S (101) ≧2.0.

[0046] According to the invention, the precursor has an integrated area S of the (001) crystal plane obtained by XRD. (101) and the integral area S of the (101) crystal plane (104) is S (001) / S (101)≧2.0.

[0047] The present invention further provides a method for preparing a lithium oxide-containing cathode material precursor, the method comprising: (1) contacting and mixing a solution or suspension of a nickel salt, a manganese salt, and a compound containing M to obtain a mixed salt solution; (2) flowing the mixed salt solution, the precipitant solution, and the complexing agent solution into a reaction vessel to carry out a crystallization reaction, and subjecting the resulting slurry to solid-liquid separation, washing, heat treatment, and sieving to obtain a lithium oxide-containing positive electrode material precursor.

[0048] In the present invention, the inventors of the present invention found that for metal hydroxide precursors, the crushing strength of the precursors is insufficient during compounding and sintering, which leads to the collapse of the prepared positive electrode material, the tap density is reduced, and the electrochemical performance is deteriorated. In the present invention, the synthesis of a highly crystalline and dense precursor is achieved by controlling the synthesis process of the precursor, such as the concentration and type of complexing agent, the concentration of precipitating agent, the stirring strength, the reaction temperature, additives, the solid content and the feed rate, etc., and the crystallinity, tap density and crushing index of the precursor material are improved by adjusting the particle size distribution and specific surface area of ​​the precursor, and the crushing index of the precursor is improved by adding suitable additives and adjusting the microstructure and morphology of the precursor.

[0049] According to the present invention, nickel salt, manganese salt or M element-containing additive is dissolved in a mixed salt solution with a molar ratio of u:v:γ and a concentration of 1-3 mol / L, M-containing compound is added to water to prepare a certain concentration of M solution or suspension, alkali is dissolved in an alkali solution with a concentration of 2-10 mol / L, and complexing agent is dissolved in a complexing agent solution with a concentration of 2-13 mol / L.

[0050] According to the present invention, the solid content of the slurry is 200-1000 g / L, preferably 300-800 g / L.

[0051] According to the present invention, the Ni-Mn mixed salt solution, the alkali solution, the complexing agent solution, and the M solution are fed through their respective liquid feed pipelines into a reaction vessel equipped with an overflow pipeline, and the stirring speed is kept constant while the liquid feed flow rates of the mixed salt solution, the precipitant solution, the complexing agent solution, and the M solution are controlled.

[0052] According to the present invention, the reaction conditions are: reaction temperature is 40-70° C., reaction pH is 10.6-12.5, and reaction time is 5-100 h.

[0053] According to the invention, the nickel salt is one or more of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate.

[0054] According to the invention, the manganese salt is one or more of manganese sulfate, manganese chloride, manganese nitrate, manganese acetate.

[0055] According to the present invention, the M-containing compound is one or more of sulfates, chlorides, nitrates, acetates, citrates, carbonates, phosphates, oxalates, and fluorides containing the M element.

[0056] According to the present invention, the precipitating agent is an alkaline substance, and the alkali is one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide.

[0057] According to the invention, the complexing agent is one or more of the following: salicylic acid, ammonium sulfate, ammonium chloride, aqueous ammonia, sulfosalicylic acid, ethylenediaminetetraacetic acid.

[0058] According to the present invention, the sintering precision (including sintering temperature, heating rate, sintering atmosphere, etc.) in the preparation process of the lithium-containing metal oxide is also very important, and affects the crushing index of the material.

[0059] A third aspect of the present invention provides a method for preparing a lithium oxide-containing cathode material, said method comprising: S1: Mix a precursor having the chemical formula represented by formula (1), a lithium source, and an additive containing an optional element M2 uniformly, and subject the mixed material to primary sintering in an atmosphere furnace to obtain a primary sintered material having the chemical formula represented by formula (2); S2: Mix the primary sintered material and an additive containing an element M' uniformly, and subject the mixed material to secondary sintering in an atmosphere furnace to obtain a lithium-containing metal oxide having the chemical formula represented by formula (3), including: Ni u Mn v M 1γ (OH)2, formula (1) where u + v + γ = 1, 0.2 < u < 1, 0 < v ≤ 0.75, 0 ≤ γ ≤ 0.35, and M1 is at least one selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, Na, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B; Li[Li a Ni x Mn y M j O2, formula (2), Li[Li a Ni x Mn y M j O2@M′, formula (3), where, in formula (2) and formula (3), 0 ≤ a ≤ 0.3, 0.2 < x < 1, 0 < y ≤ 0.75, 0 < j ≤ 0.35; M includes the M1 element in the precursor and the M2 element introduced during the primary sintering process; M1 and M2 may be the same or different, and each is at least one selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B; In formula (3), M′ is an oxide, phosphide, sulfide, fluoride, or chloride containing at least one element of Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B, and the molar content of the cation in M′ is w, where 0 < w / (a + x + y + j) ≤ 0.1.

[0060] According to the present invention, the M element in the positive electrode material originates from the M1 element in the precursor and the additive containing the M2 element introduced in the primary sintering process.

[0061] According to the present invention, the lithium source is at least one of lithium hydroxide, lithium carbonate, and lithium nitrate.

[0062] According to the present invention, the additive containing the M2 element is at least one selected from the group consisting of oxides, hydroxides, oxyhydroxides, phosphates, fluorides, borides, and carbonates containing the element M2.

[0063] According to the present invention, the M1 element, the M2 element, and the M element may be the same or different, and are each at least one selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B.

[0064] According to the present invention, the additive containing the element M' is at least one selected from the group consisting of oxides, hydroxides, oxyhydroxides, phosphates, fluorides, borides, nitrides, carbonates, and oxalates containing the element M'.

[0065] According to the invention, the molar ratio Li / (Ni+Mn+M1+M2) of the sum of the amount of the lithium source used and the amount of the additive containing the precursor and element M2 used is 1-1.85, preferably 1-1.5.

[0066] According to the present invention, the additive containing the element M2 is added in such an amount that M2 / (Ni+Mn+M1+M2) is 0.0005-0.3, preferably 0.001-0.2.

[0067] According to the present invention, the molar ratio M' / (Ni+Mn+M1+M2) of the amount of the additive containing the element M' to the amount of the primary sintered material is 0-0.1, preferably 0.001-0.02.

[0068] According to the present invention, when the molar ratio of Ni / Mn is greater than 1, i.e., x / y>1, the relationship between the primary sintering temperature T1 and the Ni content satisfies 550×(2−x)≦T1≦400×(3−x)°C, and the sintering time is 6-20h, preferably 8-15h.

[0069] According to the present invention, when the molar ratio of Ni / Mn is ≦1, i.e., y / x≧1, the relationship between the primary sintering temperature T2 and the Mn content satisfies 500×(1+y)≦T2≦650×(1+y)°C, and the sintering time is 6-20h, preferably 8-15h.

[0070] According to the present invention, when x<0.5, the atmosphere for the primary sintering and the secondary sintering is air; when 0.5≦x<0.6, the atmosphere for the primary sintering and the secondary sintering is air or a mixed gas of air and oxygen; and when x≧0.6, the atmosphere for the primary sintering and the secondary sintering is oxygen or a mixed gas of oxygen and air.

[0071] A fourth aspect of the present invention provides a lithium oxide-containing positive electrode material prepared by the above-mentioned method for preparing a lithium oxide-containing positive electrode material.

[0072] A fifth aspect of the present invention provides a cathode sheet, comprising at least 90 wt % of a lithium oxide-containing cathode material, based on the total weight of the cathode sheet, the lithium oxide-containing cathode material being the lithium oxide-containing cathode material described above.

[0073] According to the present invention, the mass occupancy rate of the positive electrode material is preferably 95% or more.

[0074] According to the present invention, the electrode sheet density of the positive electrode sheet is ≧2.8 g / cm 3 , preferably ≧3.2 g / cm 3 , more preferably ≧3.5 g / cm 3 It is.

[0075] A sixth aspect of the present invention provides the use of the lithium oxide-containing positive electrode material as described above, the lithium oxide-containing positive electrode material precursor as described above, or the positive electrode sheet as described above in a lithium ion battery.

[0076] The present invention will now be described in detail with reference to the following examples.

[0077] In the following examples and comparative examples, Unless otherwise stated, all ingredients are commercially available.

[0078] In the following examples, the relevant performance is obtained in the following manner. (1) Material phase test: Tested using a 9kW model X-ray diffraction apparatus from Rigaku Co., Ltd. (2) Morphological test: Tested with a scanning electron microscope (S-4800 model) of Hitachi, Ltd., Japan. (3) Particle size test: Tested by Marvern Hydro 2000mu model laser granulometer; (4) Specific surface area: Tested by a Tristar II3020 model specific surface area tester manufactured by Micromertics, USA. (5) Tap density: Tested by Hyakutoku's BT-30 model tap density tester. (6) Compaction density: Tested by Mitsubishi Chemical Japan's MCP-PD51 model powder impedance tester; (7) Crush index test: The material is compressed at a certain pressure using a manual tablet press of the 4350 model made by Carver, USA, and the particle size test is performed on the material after crushing. The result is calculated by substituting the crush index formula. (8) Surface residual alkali test: measured by titration using Metrohm888 professional Tirando intelligent potential titrator; (9) Thermal stability test: Tested by Mettler TGA-DSC3 model thermogravimetric analyzer; (10) Electrochemical performance test: The electrochemical performance of the prepared lithium oxide-containing positive electrode material was tested on a 2025-type buckle battery using a Xinwei battery test system. Specifically, 1) Manufacturing process of 2025 type buckle battery: Electrode sheet production: The lithium oxide-containing positive electrode material, carbon black, and polyvinylidene fluoride were thoroughly mixed in a certain mass ratio with an appropriate amount of N-methylpyrrolidone to form a uniform slurry, which was then applied to an aluminum foil, dried at 120°C, roll-pressed, and punched out to produce a positive electrode sheet with a diameter of 11 mm.

[0079] Battery assembly: A Li metal piece with a diameter of 17 mm and a thickness of 1 mm is used for the negative electrode, a polyethylene porous film with a thickness of 25 μm is used for the separator, and a mixture of 1 mol / L LiPF6, ethylene carbonate (EC), and diethyl carbonate (DEC) in equal amounts is used for the electrolyte.

[0080] The positive electrode sheet, separator, negative electrode sheet and electrolyte are assembled into a 2025-type buckle battery in an Ar gas glove box in which the water content and oxygen content are both less than 5 ppm, and the battery at this stage is designated as an inactivated battery.

[0081] 2) Electrochemical performance test: When the molar ratio of Ni / Mn is greater than 1, that is, x / y>1, the buckle battery test conditions are as follows: the buckle battery is prepared and left for 2 hours, and after the open circuit voltage is stabilized, it is charged to a cut-off voltage of 4.3V at a positive current density of 0.1C, charged at a constant voltage for 30min, and then discharged to a cut-off voltage of 3.0V at the same current density, and the battery is treated as an activated battery. The activated battery is used to perform a charge-discharge test at 0.1C in the voltage range of 3.0-4.3V, 25℃, and the charge-discharge range of 3.0-4.3V to evaluate the charge-discharge capacity of the material; the activated battery is used to perform a charge-discharge test at 0.1C, 0.2C, 0.33C, 0.5C, and 1C to evaluate the rate characteristics of the material at the ratio of the 1C capacity to the 0.1C capacity; and the cycle performance of the material is evaluated by cycling 80 times at 1C in the 3.0-4.4V range.

[0082] When the molar ratio of Ni / Mn is 1 or less, that is, x / y≦1, the buckle battery test conditions: the buckle battery is left for 2 hours after preparation, and after the open circuit voltage is stabilized, it is charged to a cut-off voltage of 4.6V at a positive electrode current density of 0.1C, charged at a constant voltage for 30 minutes, and then discharged to a cut-off voltage of 2.0V at the same current density, and the battery at this time is called an activated battery. The activated battery is used to perform a charge / discharge test at a voltage range of 2.0 to 4.6V, 25°C, a charge / discharge range of 2.0 to 4.6V, and 0.1C to evaluate the charge / discharge capacity of the material, and the activated battery is used to perform a charge / discharge test at 0.1C, 0.2C, 0.33C, 0.5C, and 1C to evaluate the rate characteristics of the material at the ratio of the 1C capacity to the 0.1C capacity, and the cycle performance of the material is evaluated by cycling 80 times at 0.5C in the 2.0 to 4.6V range.

[0083] Example 1 This example is intended to illustrate the lithium oxide-containing positive electrode material prepared in accordance with the present invention.

[0084] Nickel sulfate and manganese sulfate are dissolved in a metal molar ratio of 5:3 to obtain a 2 mol / L mixed salt solution, cobalt sulfate and aluminum sulfate are dissolved in metal molar ratios of Co / (Ni+Mn+Co+Al) = 0.18 and Al / (Ni+Mn+Co+Al) = 0.02 to obtain a 2 mol / L mixed salt solution, sodium hydroxide is dissolved to obtain an alkaline solution with a concentration of 6 mol / L, and ammonia water is dissolved to obtain a complexing agent solution with a concentration of 5 mol / L.

[0085] Next, 20L of the mixed salt solution, the alkali solution, and the complexing agent solution were fed into the reactor together to react. During the process, the stirring speed was kept constant at 600 revolutions / min. At the same time, the mixed salt solution flow rate was controlled to 300mL / h, the reaction pH to 11.6, the reaction temperature to 50℃, and the ammonia concentration in the reaction system to 9g / L. The reaction was carried out in N2 gas. The reaction was retained for 60 hours, and the solid content was 500g / L. The slurry obtained by the precipitation crystallization reaction was separated into solid and liquid and washed. It was then dried at 105℃ for 10 hours and sieved to obtain spherical Ni. 0.5 Mn 0.3 Co 0.18 Al0.02 The (OH)2 precursor material is obtained and recorded as P-1.

[0086] The precursor P-1, lithium carbonate, and additives TiO2 and WO3 were mixed uniformly in a high-speed mixer at the ratio of Li: (Ni+Mn+Co+Al+Ti+W) = 1.03, Ti: (Ni+Mn+Co+Al+Ti+W) = 0.003, and W: (Ni+Mn+Co+Al+Ti+W) = 0.002. The mixture was heated to 920°C in an air atmosphere, held for 10 hours, and cooled naturally to obtain the primary sintered positive electrode material Li[Li0Ni 0.4975 Mn 0.2985 Co 0.1791 Al 0.0199 Ti 0.003 W 0.002 ]O2 is obtained and recorded as S-1.

[0087] The primary sintered material S-1, additives Nb2O5 and La2O3 were uniformly mixed with Nb: (Ni+Mn+Co+Al+Ti+W) = 0.002, La: (Ni+Mn+Co+Al+Ti+W) = 0.002, heated to 650°C in an air atmosphere, held for 6 hours, and cooled naturally to obtain the secondary sintered positive electrode material Li[Li0Ni 0.4975 Mn 0.2985 Co 0.1791 Al 0.0199 Ti 0.003 W 0.002 ]O2@Nb 0.002 La 0.002 is obtained and recorded as FS-1.

[0088] Example 2-14 This example is intended to illustrate the lithium oxide-containing positive electrode material prepared in accordance with the present invention.

[0089] The lithium oxide-containing positive electrode material was prepared in the same manner as in Example 1, with the difference being that the precursor preparation process, the preparation process of the primary sintered positive electrode material, and the preparation process of the secondary sintered positive electrode material were different, as shown in Table 1.

[0090] [Table 1-1]

[0091] [Table 1-2]

[0092] [Table 1-3]

[0093] [Table 1-4]

[0094] [Table 1-5]

[0095] [Table 1-6]

[0096] [Table 1-7]

[0097] [Table 1-8]

[0098] [Table 1-9]

[0099] In Table 1, unless otherwise specified, all ratios and usage ratios are molar ratios.

[0100] Comparative Example 1

[0101] The same synthesis method and conditions as in Example 5 were used, except that the primary sintering temperature was adjusted to 600° C. The obtained positive electrode material was designated D-1 and is shown in Table 2.

[0102] Comparative Example 2 The same synthesis method and conditions as in Example 5 were used, except that the primary sintering temperature was adjusted to 900° C. The obtained positive electrode material was designated D-2 and is shown in Table 2.

[0103] Comparative Example 3 The same synthesis method and conditions as in Example 5 were adopted, and the additives rhenium oxide and samarium oxide were not added in the preparation process of the primary sintered positive electrode material. The obtained positive electrode material was designated as D-3 and is shown in Table 2.

[0104] Comparative Example 4 The same synthesis method and conditions as in Example 5 were used, and the additives tungsten nitride and aluminum fluoride were not added in the secondary sintered positive electrode material preparation process. The obtained positive electrode material was designated D-4 and is shown in Table 2.

[0105] Comparative Example 5 The same synthesis method and conditions as in Example 9 were adopted, and the solid content was adjusted to 150 g / L only in the precursor preparation process. The obtained positive electrode material was designated as D-5 and is shown in Table 2.

[0106] Comparative Example 6 The same synthesis method and conditions as in Example 9 were adopted, and only the preparation process of the primary sintered positive electrode material was performed without adding the additives tungsten oxide and hydroxyl alumina. The obtained positive electrode material was designated as D-6 and is shown in Table 2.

[0107] Comparative Example 7 The same synthesis method and conditions as in Example 9 were adopted, except for the preparation process of the secondary sintered positive electrode material. The obtained positive electrode material was designated as D-7 and is shown in Table 2.

[0108] [Table 2-1]

[0109] [Table 2-2]

[0110] [Table 2-3]

[0111] [Table 2-4]

[0112] [Table 2-5]

[0113] Test example 1 The performance of the lithium oxide-containing positive electrode material precursor prepared in Examples 1-14 and Comparative Examples 1-7 was tested, and the results are shown in Table 3. The performance of the lithium oxide-containing positive electrode material prepared in Examples 1-14 and Comparative Examples 1-7 was tested, and the results are shown in Table 4 and Table 5.

[0114] [Table 3]

[0115] [Table 4-1]

[0116] [Table 4-2]

[0117] [Table 4-3]

[0118] [Table 5]

[0119] Test example 2 The lithium oxide-containing positive electrode materials prepared in Examples 1-14 and Comparative Examples 1-7 are used as the positive electrode sheets of lithium ion batteries to prepare lithium ion batteries, and the performance of the lithium ion batteries is tested. The results are shown in Table 6.

[0120] [Table 6-1]

[0121] [Table 6-2]

[0122] [Table 6-3]

[0123] In addition, in the present invention, Fig. 1 is a schematic diagram comparing the charge and discharge curves of Example 5 and Comparative Example 1. From Fig. 1, by comparing the charge and discharge curves of Example 5 and Comparative Example 1, it can be seen that the 0.1C discharge capacity (225.2 mAh / g) of the positive electrode material provided by Example 5 is higher than the 0.1C discharge capacity (216.9 mAh / g) of the positive electrode material D-1 obtained when the primary sintering temperature was too low (600°C).

[0124] Figure 2 is a schematic diagram comparing the cycle performance of Example 5 and Comparative Example 1. From Figure 2, by comparing the cycle performance of Example 5 and Comparative Example 1, it can be seen that the capacity retention rate of Example 5 (94.6%) is significantly higher than the capacity retention rate of the positive electrode material provided by D-1 (86.7%). This is because when the sintering temperature is too low, the primary crystal grain growth and development is incomplete, the crushing index is low, and the structure is unstable, resulting in low capacity and cycle performance.

[0125] Fig. 3 is a schematic diagram comparing the charge and discharge curves of Example 5 and Comparative Example 2. From Fig. 3, by comparing the charge and discharge curves of Example 5 and Comparative Example 2, it can be seen that the 0.1C discharge capacity (225.2mAh / g) of the positive electrode material provided by Example 5 is higher than the 0.1C discharge capacity (208.3mAh / g) of the positive electrode material D-2 obtained when the primary sintering temperature was too high (900°C).

[0126] 4 is a schematic diagram comparing the cycle performance of Example 5 and Comparative Example 2. From FIG. 4, by comparing the cycle performance of Example 5 and Comparative Example 2, it can be seen that the capacity retention rate of Example 5 (94.6%) is significantly higher than the capacity retention rate of the positive electrode material provided by D-2 (85.9%). This is because when the sintering temperature is too high, the growth and development of primary crystal grains is excessive, resulting in a low crushing index and an unstable structure, resulting in low capacity and cycle performance.

[0127] Fig. 5 is a schematic diagram comparing the charge / discharge curves of Example 5 and Comparative Example 3. From Fig. 5, by comparing the charge / discharge curves of Example 5 and Comparative Example 3, it can be seen that the 0.1C discharge capacity (225.2mAh / g) of Example 5 is higher than the 0.1C discharge capacity (221.7mAh / g) of the positive electrode material D-3 obtained without adding rhenium oxide and samarium oxide additives to the primary sintering.

[0128] FIG. 6 is a schematic diagram comparing the cycle performance of Example 5 and Comparative Example 3. From FIG. 6, by comparing the cycle performance of Example 5 and Comparative Example 3, it can be seen that the capacity retention rate of Example 5 (94.6%) is significantly higher than the capacity retention rate of the positive electrode material provided by D-3 (87.5%). The above shows that the capacity and cycle performance of the material can be improved by adding rhenium oxide and samarium oxide additives to the primary sintering, which is because the microzone structure of the material can be improved by proper doping modification, and the formation of lithium-containing compounds on the particle surface or between the particles can help improve the crushing index of the material, thereby improving the electrochemical performance such as the capacity and cycle performance of the positive electrode material.

[0129] Fig. 7 is a schematic diagram comparing the charge / discharge curves of Example 5 and Comparative Example 4. From Fig. 7, by comparing the charge / discharge curves of Example 5 and Comparative Example 4, it can be seen that the 0.1C discharge capacity (225.2 mAh / g) of Example 5 is significantly higher than the 0.1C discharge capacity (214.3 mAh / g) of the positive electrode material D-4 obtained without adding tungsten nitride or aluminum fluoride additives to the secondary sintering.

[0130] FIG. 8 is a schematic diagram comparing the cycle performance of Example 5 and Comparative Example 4. From FIG. 8, by comparing the cycle performance of Example 5 and Comparative Example 4, it can be seen that the capacity retention rate of Example 5 (94.6%) is significantly higher than the capacity retention rate of the positive electrode material provided by D-4 (86.6%). The above shows that the capacity and cycle performance of the material can be improved by adding tungsten nitride and aluminum fluoride additives to the secondary sintering, which can form a stable coating layer on the surface of the material, improve the surface microzone structure of the material, reduce the side reaction on the surface of the material, and also help improve the crushing index of the material, thereby improving the electrochemical performance such as the capacity and cycle performance of the positive electrode material.

[0131] Fig. 9 is a schematic diagram comparing the charge / discharge curves of Example 9 and Comparative Example 5. From Fig. 9, by comparing the charge / discharge curves of Example 9 and Comparative Example 5, it can be seen that the 0.1C discharge capacity (250.7mAh / g) of Example 9 is significantly higher than the 0.1C discharge capacity (240.9mAh / g) of the positive electrode material D-5 obtained when the solid content was reduced to 150g / L in the precursor preparation process.

[0132] Figure 10 is a schematic diagram comparing the cycle performance of Example 9 and Comparative Example 5. From Figure 10, by comparing the cycle performance of Example 9 and Comparative Example 5, it can be seen that the capacity retention rate of Example 9 (93.9%) is significantly higher than the capacity retention rate of the positive electrode material provided by D-5 (88.0%). This is because the low solid content leads to poor crystallinity and compactness of the precursor, and also changes the morphology and microstructure, resulting in a low crushing index, which deteriorates the electrochemical performance such as the capacity and cycle performance of the material.

[0133] Fig. 11 is a schematic diagram comparing the charge / discharge curves of Example 9 and Comparative Example 6. From Fig. 11, by comparing the charge / discharge curves of Example 9 and Comparative Example 6, it can be seen that the 0.1C discharge capacity (250.7mAh / g) of Example 9 is significantly higher than the 0.1C discharge capacity (241.9mAh / g) of the positive electrode material D-6 obtained without adding tungsten oxide and hydroxyl alumina additives to the primary sintering.

[0134] FIG. 12 is a schematic diagram comparing the cycle performance of Example 9 and Comparative Example 6. From FIG. 12, by comparing the cycle performance of Example 9 and Comparative Example 6, it can be seen that the capacity retention rate of Example 9 (93.9%) is significantly higher than the capacity retention rate of the positive electrode material provided by D-6 (89.0%). The above shows that the capacity and cycle performance of the material can be improved by adding tungsten oxide and hydroxyl alumina additives to the primary sintering, which is because the microzone structure of the material can be improved by proper doping modification, and the formation of lithium-containing compounds on the particle surface or between the particles can help improve the crushing index of the material, thereby improving the electrochemical performance such as the capacity and cycle performance of the positive electrode material.

[0135] Fig. 13 is a schematic diagram comparing the charge / discharge curves of Example 9 and Comparative Example 7. From Fig. 13, by comparing the charge / discharge curves of Example 9 and Comparative Example 7, it can be seen that the 0.1C discharge capacity (250.7 mAh / g) of Example 9 is significantly higher than the 0.1C discharge capacity (233.0 mAh / g) of the positive electrode material D-7 obtained without the secondary sintering process.

[0136] FIG. 14 is a schematic diagram comparing the cycle performance of Example 9 and Comparative Example 7. From FIG. 14, by comparing the cycle performance of Example 9 and Comparative Example 7, it can be seen that the capacity retention rate of Example 9 (93.9%) is significantly higher than the capacity retention rate of the positive electrode material provided by D-7 (89.9%). The above shows that the secondary sintering effectively improves the capacity and cycle performance of the material, because the secondary sintering process can form a stable coating layer on the surface of the material, rearrange the atoms on the surface of the material, improve the surface microzone structure of the material, reduce the side reactions on the surface of the material, and also help improve the crushing index of the material, thereby improving the electrochemical performance such as the capacity and cycle performance of the positive electrode material.

[0137] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited thereto. Within the technical scope of the present invention, the technical solutions of the present invention may be modified in various simple ways, including combining each technical feature in any other suitable manner, and these simple modifications and combinations are also considered as the contents disclosed in the present invention, and all belong to the protection scope of the present invention.

Claims

1. A lithium oxide-containing positive electrode material, comprising: a crushing index Δλ (P 100 ) is Δλ(P 100 ) ≧60% + (y / x) × 5%, Here, y / x is a molar ratio of Mn / Ni in the positive electrode material.

2. The crushing index Δλ (P 200 ) is Δλ(P 200 ) ≧ 45% + (y / x) × 5%, And / or the crushing index Δλ (P 300 ) is Δλ(P 300 2. The lithium oxide-containing positive electrode material according to claim 1, wherein y / x satisfies ≧35%+(y / x)×5%.

3. The lithium oxide-containing positive electrode material has a chemical formula represented by formula (3), Li[Li a Ni x Mn y M j O 2 @M′, Formula (3) wherein 0≦a≦0.3, 0.2<x<1, 0<y≦0.75, 0<j≦0.35, M is at least one element selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B, M′ is an oxide, phosphide, sulfide, fluoride, or chloride containing at least one element of Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B, the molar content of cations in M′ is w, and 0<w / (a+x+y+j)≦0.1, 3. The lithium oxide-containing positive electrode material according to claim 1, wherein preferably, 0.02≦a≦0.2, 0.3<x<0.9, 0.05<y≦0.68, 0<j≦0.3, and 0.001<w / (a+x+y+j)≦0.02, M is at least one element selected from Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Ta, and B, and M′ is an oxide, phosphide, sulfide, or fluoride containing at least one element selected from Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Ta, and B.

4. The compaction density of the lithium oxide-containing positive electrode material is ≧2.8 g / cm 3 , preferably ≧3 g / cm 3 , more preferably ≧3.2 g / cm 3 and And / or, the tap density of the lithium oxide-containing positive electrode material is ≧1.7 g / cm 3 , preferably ≧2 g / cm 3 , more preferably ≧2.4 g / cm 3 and And / or, the content of the surface soluble alkali of the lithium oxide-containing positive electrode material is Li 2 CO 3 ≦1 wt%, LiOH≦0.5 wt%, Preferably Li 2 CO 3 ≦0.5 wt %, LiOH≦0.4 wt %, More preferably, Li 2 CO 3 ≦0.3wt%, LiOH≦0.3wt%, Even more preferably Li 2 CO 3 ≦0.2wt%, LiOH≦0.2wt%, and / or The lithium oxide-containing positive electrode material has a half-width FWHM of the (003) crystal plane obtained by XRD. (003) and FWHM of the (104) crystal plane (104) teeth, 0.10≦FWHM (003) ≦0.25, preferably 0.13≦FWHM (003) ≦0.22, 0.20≦FWHM (104) ≦0.50, preferably 0.22≦FWHM (104) ≦0.42 is satisfied, and / or The lithium oxide-containing positive electrode material has a peak area S of a (003) crystal plane obtained by XRD. (003) and the peak area S of the (104) crystal plane (104) teeth, 1.1≦S (003) / S (104) ≦1.8, preferably 1.2≦S (003) / S (104) The lithium oxide-containing positive electrode material according to any one of claims 1 to 3, which satisfies ≦1.

6.

5. A lithium oxide-containing positive electrode material precursor, the crushing index Δλ′(P 50 ) is Δλ'(P 50 ) ≧35% + (v / u) × 8%, wherein v / u is the molar ratio of Mn / Ni in the precursor.

6. The crushing index Δλ′ (P 100 ) is Δλ'(P 100 6. The lithium oxide-containing positive electrode material precursor according to claim 5, wherein the lithium oxide-containing positive electrode material precursor satisfies the following:

7. 1. A method for preparing a lithium oxide-containing positive electrode material, the method comprising: S1: A precursor having the chemical formula represented by formula (1), a lithium source, and an optional element M 2 A step of uniformly mixing the contained additives and performing primary sintering in an atmospheric furnace to obtain a primary sintered material having a chemical formula represented by formula (2); S2: uniformly mixing the primary sintering material and the element M′-containing additive, and subjecting the mixed material to secondary sintering in an atmospheric furnace to obtain a lithium-containing metal oxide having a chemical formula represented by formula (3); Ni u Mn v M 1γ (OH) 2 , formula (1) Here, u+v+γ=1, 0.2<u<1, 0<v≦0.75, 0≦γ≦0.35, and M 1 is at least one element selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, Na, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B; Li[Li a Ni x Mn y M j O 2 、Formula (2) Li[Li a Ni x Mn y M j O 2 @M′, Formula (3) Here, in equations (2) and (3), a+x+y+j=1, 0≦a≦0.3, 0.2<x<1, 0<y≦0.75, and 0<j≦0.35, M is M in the precursor 1 Elements and M introduced during the primary sintering process 2 Contains the elements, M 1 , M. 2 may be the same or different, and each is at least one element selected from Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta, and B; In equation (3), A method for preparing a lithium oxide-containing positive electrode material, characterized in that M' is an oxide, phosphide, sulfide, fluoride or chloride containing at least one element selected from the group consisting of Al, Zr, Nb, Ti, Y, Sc, Cr, Co, W, Mg, La, Os, Pr, Re, Ru, Sr, Sm, Ta and B, and the molar content of cations in M' is w, where 0<w / (a+x+y+j)≦0.

1.

8. When the molar ratio of Ni / Mn is greater than 1, i.e., x / y>1, the sintering temperature T 1 The relationship between the Ni content and the T 1 ≦400×(3−x)° C., and the sintering time is 6 to 20 hours, preferably 8 to 15 hours; And / or, when the molar ratio of Ni / Mn is ≦1, i.e., y / x ≧1, the sintering temperature T 2 The relationship between the Mn content and the T 2 ≦650×(1+y)° C., and the sintering time is 6 to 20 hours, preferably 8 to 15 hours; and / or the atmosphere of the primary sintering and the secondary sintering is air when x<0.5, the atmosphere of the primary sintering and the secondary sintering is air or a mixed gas of air and oxygen when 0.5≦x<0.6, and the atmosphere of the primary sintering and the secondary sintering is oxygen or a mixed gas of oxygen and air when x≧0.

6.

9. A lithium oxide-containing positive electrode material prepared by the method for preparing a lithium oxide-containing positive electrode material according to claim 7 or 8.

10. a positive electrode sheet comprising at least 90 wt % of a lithium oxide-containing positive electrode material based on a total weight of the positive electrode sheet; The lithium oxide-containing positive electrode material is the lithium oxide-containing positive electrode material according to any one of claims 1 to 4 and 9.

11. The electrode sheet density of the positive electrode sheet is ≧2.8 g / cm 3 , preferably ≧3.2 g / cm 3 , more preferably ≧3.5 g / cm 3 The positive electrode sheet according to claim 10 .

12. Use of the lithium oxide-containing positive electrode material according to any one of claims 1 to 4 and 9, the lithium oxide-containing positive electrode material precursor according to claim 5 or 6, or the positive electrode sheet according to claim 10 or 11 in a lithium ion battery.

Citation Information

Patent Citations

  • Preparation method for high-nickel ternary material of lithium ion battery

    CN109473652A

  • Pressure-resistant positive electrode active material and electrochemical energy storage device

    CN111384371A

  • Compound powder, method for producing the same, and use thereof in lithium secondary batteries

    JP2010505732A

  • Positive electrode active material powder for lithium secondary battery, method for manufacturing the same, and lithium secondary battery

    JP2012253009A

  • Positive electrode active material for lithium ion battery, positive electrode for lithium ion battery, and lithium ion battery

    JP2014199778A